2009
DOI: 10.1590/s0100-879x2009000100016
|View full text |Cite
|
Sign up to set email alerts
|

GABA in the central amygdaloid nucleus modulates the electrolyte excretion and hormonal responses to blood volume expansion in rats

Abstract: We investigated the involvement of GABAergic mechanisms of the central amygdaloid nucleus (CeA) in unanesthetized rats subjected to acute isotonic or hypertonic blood volume expansion (BVE). Male Wistar rats bearing cannulas unilaterally implanted in the CeA were treated with vehicle, muscimol (0.2 nmol/0.2 μL) or bicuculline (1.6 nmol/0.2 μL) in the CeA, followed by isotonic or hypertonic BVE (0.15 or 0.3 M NaCl, 2 mL/100 g body weight over 1 min). The vehicle-treated group showed an increase in sodium excret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…We have previously shown that, in rats pre‐treated with the GABAergic agonist muscimol in the CeA, which is rich in GABA A receptors, there was a reduction in plasma OT and ANP hormone levels, as well as in sodium excretion and urine output in response to hypertonic BVE. These responses are similar to the effects of the OT receptor antagonist OVT in the CeA on the BVE and OT induced responses observed in the present study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We have previously shown that, in rats pre‐treated with the GABAergic agonist muscimol in the CeA, which is rich in GABA A receptors, there was a reduction in plasma OT and ANP hormone levels, as well as in sodium excretion and urine output in response to hypertonic BVE. These responses are similar to the effects of the OT receptor antagonist OVT in the CeA on the BVE and OT induced responses observed in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Margatho et al . also showed that the involvement of GABAergic mechanisms within the CeA is related to the control of urinary electrolyte excretion and hormone release in rats subjected to acute isotonic or hypertonic BVE. It was observed that in response to BVE, a previous injection of muscimol into the CeA inhibited the synaptic inputs mediated by the perinuclear GABAergic interneurones in the Pa and SON.…”
mentioning
confidence: 87%
“…Furthermore, increases in urine output, renal sodium excretion, and plasma OT and ANP concentrations induced by isotonic and hypertonic EVE are attenuated in rats pretreated with muscimol into the CeA. Bicuculline, an antagonist of GABA A receptors, injected into the CeA, also reduced the effects of hypertonic EVE on urinary volume and ANP secretion 39. Thus, taken together, these data suggest that the CeA GABAergic mechanisms are involved in the control of ANP and OT secretion, as well as in the control of sodium and water excretion in response to isotonic and hypertonic increases in the ECF.…”
Section: Main Neural Pathways Involved In the Regulation Of Ecf Volummentioning
confidence: 95%
“…Cofiel and Mattioli (3), also using L-histamine, evaluated the role of the histaminergic system in learning and stress and showed its importance in the modulation of these responses in zebrafish. The study by Margatho et al (4) suggested that central amygdala GABAergic mechanisms are involved in atrial natriuretic peptide and oxytocin secretion in response to blood volume expansion. Nascimento and Branco (5) suggested an interesting synergism between peripheral and spinal heme oxygenase-carbon monoxide pathways that may play an antinociceptive role.…”
mentioning
confidence: 99%